Micronutrient status in soybean (Glycine max) - wheat (Triticum aestivum) cropping system in Kumaon region of Uttaranchal - GHOSH, B N; PRAKAS, VED; SINGH, R D (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1993-99 to assess the yield response to farmyard manure application and its fate on build up/depletion in soil and uptake of Fe, Mn, Zn and Cu in soybean [Glycine max (L.) Merr.]-wheat (Triticum aestivum L. emend. Fiori and Paol.) rotation in a long-term field experiments. Yield response curve showed sharp increase in response to farmyard manure application in soybean and succeeding wheat crop. Change in micronutrient showed that zinc levels were below the critical level in NPK treatment (